Edukasi dan Pelatihan Pengolahan Limbah Diapers menjadi Pupuk Tanaman pada Warga Kelurahan Sendangguwo Semarang - Andarina Aji Pamurti; Dwi Prabowo (Universitas Semarang, 2023)
Diapers waste generated by residents of RT 04 and RT 08/ RW 07 Sendangguwo Village, Semarang City has a large amount. Diapers waste is difficult to decompose by soil microbes. The decomposition process takes up to hundreds of years. The amount of diapers waste is quite large and disposed of anywhere can have a negative impact on the environment. Diapers waste can be used to make useful products. The absorbent gel can be used as plant fertilizer. The gel is very good at absorbing water so it can retain soil moisture and become nutrients for plants. However, not many people know about the impact of diapers waste and do not know that diapers waste can be made into useful products. It is necessary to provide knowledge about the negative impacts of diapers waste which can pollute the environment. Then it was continued with training on diaper waste management to become plant fertilizer for residents in the Sendangguwo Village, Tembalang District, Semarang City. The implementation method used is by giving socialization and hands-on practice regarding the stages of processing diapers waste into plant fertilizer. The results of the training were in the form of plant fertilizer products from diapers waste which were then packaged in plastic containers and then handed over to the community.